Psallus thomashenryi sp. n. and Psallus lucanicus from Turkey (Hemiptera, Heteroptera, Miridae) - Attilio Carapezza; Petr Kment (ZooKeys, 2018)
Psallus (Psallus) thomashenryi sp. n. (Hemiptera: Heteroptera: Miridae: Phylinae: Phylini: Phylina) is described from southern Anatolia, Turkey. Illustrations of the dorsal habitus and male genitalia are provided. Its habitus is similar to other uniformly orange species of the subgenus Psallus Fieber, 1858, particularly P. asthenicus Seidenstücker, 1966 from which it can be easily distinguished by the combination of extremely small size (2.3 mm in both sexes) and different morphology of the vesica. Psallus (Psallus) lucanicus Wagner, 1968 is recorded for the first time from Turkey. Psallus (Psallus) aurora (Mulsant & Rey, 1852) is removed from the list of Turkish fauna based on a reevaluation of the voucher specimen. An updated checklist of the species of Psallus known to occur in Turkey is provided. The relevance of Anatolia and the Syro-anatolian-transcaucasian region in the Palearctic distribution of Psallus is discussed. The westernmost record of another mirid, Plagiognathus marivanensis Linnavuori, 2010, is provided.